Malaysian response on challenges facing the global economy of palm oil - Shehu, Sani (Indonesian Journal of Multidisciplinary Science, 2025)
The Covid-19 pandemic has impacted on the global economy of palm oil. This paper explores the Malaysian response on the challenges raised by the western countries on palm oil, and how Malaysia responds to these challenges as well as the recent trend of Covid-2019. The study employs a qualitative exploratory design to collect and analyze data, with primary data gathered through semi-structured, open-ended interviews conducted face-to-face, involving three carefully selected participants from Malaysia to ensure diverse perspectives. The research uses qualitative document analysis to interpret the data and draw meaningful conclusions. The results show that the Covid-18 pandelic impacted Malaysia's palm oil global economy by decreasing the global demand, disrupting the trade, restricting labour mobility and declining production. As a result of these challenges, Malaysia government responded with certain formulated policies in form of phases which were implemented as first Movement Control Order (MCO) from 18th March 2020 to 3rd May 2020. The Malaysian Sustainable Palm Oil (MSPO) certification scheme was effective in enhancing market access and consumer perception would provide valuable insights into its role in promoting sustainability. Moreover, examining innovative uses of the palm oil by-products and their potential to mitigate environmental impacts could contribute significantly to sustainable production practices. Finally, evaluating the effectiveness of ongoing policies related to deforestation and land use, alongside stakeholder perspectives, would deepen the understanding of how to balance economic growth with environmental stewardship in Malaysian palm oil sector.